1987
DOI: 10.1097/00000658-198707000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Right Pulmonary Artery from the Ascending Aorta

Abstract: Origin of the right pulmonary artery from the aorta is a congenital malformation usually associated with serious symptoms in the first year of life and characterized by a poor prognosis. Sixty-five patients with this disorder have been reviewed in the literature, and 95% presented during the first year with signs of congestive heart failure. All had cardiomegaly by radiographic and electrocardiographic examination. An accurate diagnosis was established by cineangiography, and associated cardiovascular anomalie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
73
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 56 publications
1
73
1
2
Order By: Relevance
“…Most commonly, the surgical correction was achieved within the first month of age, 3,4,8,13,15,20 although successful repair has been reported in adults. 16 Fontana et al 28 found a 30% 1-year survival in a series of 23 cases with anomalous origin of one pulmonary artery from the aorta which was not treated surgically. Successful correction of this anomaly in the first days of life, even in premature infants, has been reported.…”
Section: Discussionmentioning
confidence: 98%
“…Most commonly, the surgical correction was achieved within the first month of age, 3,4,8,13,15,20 although successful repair has been reported in adults. 16 Fontana et al 28 found a 30% 1-year survival in a series of 23 cases with anomalous origin of one pulmonary artery from the aorta which was not treated surgically. Successful correction of this anomaly in the first days of life, even in premature infants, has been reported.…”
Section: Discussionmentioning
confidence: 98%
“…Without surgery, the mortality in patients with AOPA is extremely high, reaching as high as 80%. [2][3][4][5] This is due to severe, rapidly progressive pulmonary vascular disease and congestive cardiac failure. Both isolated AOLPA and that associated with other defects have been well described.…”
mentioning
confidence: 99%
“…2 It involves more frequently the right than the left pulmonary artery. 1 Early development of pulmonary hypertension and irreversible pulmonary vascular changes occur inevitably. 2 In patients with AOPA, the affected lung is exposed to unrestricted aortic flow and systemic pressure, while the contralateral lung receives the entire right ventricular output in addition to flow contributed by associated anomalies, such as PDA, ventricular septal defect, and ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Embryologically, anomalous origin of the right pulmonary artery from the proximal posterior aspect of the ascending aorta is due to the incomplete leftward migration of the right sixth aortic arch. 1 Early diagnosis is essential, so that early surgical repair can be performed to improve outcome. 1 Early development of pulmonary hypertension and irreversible pulmonary vascular changes occur inevitably.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation